Association of acyl-CoA oxidase-like gene polymorphisms with risk, onset age, and beta-cell function of type 1 diabetes in Chinese - Liu, Jinhan; Xia, Ying; Xie, Zhiguo; Li, Xia; Huang, Gan; Hu, Jingyi; Zhou, Zhiguang (Frontiers in Endocrinology, 2025)
IntroductionGenome-wide association studies in Caucasians suggested an association between the acyl-CoA oxidase-like (ACOXL) gene and type 1 diabetes (T1D). We investigated if polymorphisms in ACOXL conferred susceptibility to T1D in Chinese and how they affected the clinical characteristics of T1D.MethodsMassARRAY was performed in this case–control study to genotype rs4849165 and rs4849135 of ACOXL in a collection of 1,280 patients with T1D and 1,331 non-diabetic subjects.ResultsThe minor allele C of rs4849165 was associated with an increased risk of T1D (P = 0.0013, OR 1.21). Moreover, individuals with the C/C genotype exhibited significantly lower postprandial C-peptide levels compared with T allele carriers (P = 0.0058, OR 1.76). The minor allele T of rs4849135 was associated with a decreased risk for T1D (P = 0.0098, OR 0.85) and a lower likelihood of having a low level of postprandial C-peptide (P = 0.0213, OR 0.78). Patients with G/T or T/T genotypes were more likely to be diagnosed during adulthood than those with G/G genotype (P = 0.0206, OR 0.77). No correlation with glutamic acid decarboxylase antibodies (GADA), protein tyrosine phosphatase antibodies (IA-2A), or zinc transporter 8 antibodies (ZnT8A) could be reported here.DiscussionPolymorphisms in ACOXL were associated with susceptibility to T1D in Chinese and showed associations with age at onset and beta-cell function. These loci, together with other genetic signals, may contribute to the development of risk models to identify genetically susceptible individuals in the Chinese population.